Cost-effectiveness analysis of fesoterodine flexible dose in newly diagnosed patients with overactive bladder in routine clinical practice in Spain - Peral C; Sánchez-Ballester F; García-Mediero JM; Ramos J; Rejas J (ClinicoEconomics and Outcomes Research, 2016)
Carmen Peral,1 Francisco Sánchez-Ballester,2 José M García-Mediero,3 Jaime Ramos,1 Javier Rejas1 1Health Economics & Outcomes Research Department, Pfizer, Alcobendas (Madrid), 2Department of Urology, Hospital General Universitario de Valencia, Valencia, 3Department of Urology, Hospital MD Anderson Cancer Center Madrid, Madrid, Spain Objective: To carry out cost-effectiveness analysis from the Spanish National Health System perspective, of treating overactive bladder (OAB), in newly diagnosed patients with two flexible doses of fesoterodine in routine clinical practice.Patients and methods: Economic evaluation of flexible-dose fesoterodine in newly diagnosed patients, including two treatment groups: standard escalating from 4 to 8 mg or fast escalating to 8 mg. Costs were estimated from health care resources utilization related to OAB, and were expressed in 2015 Euros. Quality-adjusted life-years (QALYs) were obtained from overactive bladder questionnaire-short form. Univariate and probabilistic sensitivity analyses were carried out.Results: Three hundred and ninety symptomatic OAB patients treated with fesoterodine and newly diagnosed (141 in fast escalating group and 249 in standard escalating) were analyzed. Adjusted health care total costs were not statistically different; difference −€4.1 (confidence interval: −153.3; 25.1) P=0.842. QALYs were higher in fast escalating to high dose vs standard escalating group, resulting in a cost of −€16,020/QALY gained for fast escalating vs standard escalating group.Conclusion: When the cost-effectiveness threshold is set at a maximum value of €30,000/QALY gained, fesoterodine fast escalating group was cost-effective vs standard escalating group 67.6% of the time. The treatment with fesoterodine, in female patients newly diagnosed, fast escalating to 8 mg was a cost-effective option relative to escalating traditionally from 4 to 8 mg, in the management of OAB in routine clinical practice, from the Spanish National Health System perspective. Keywords: antimuscarinic, fesoterodine, flexible dose, overactive bladder, cost-effectiveness